Factors affecting foraging behavior of beef cattle grazing native tallgrass range in the Kansas Flint Hills - Aubel, Nancy Ann (Kansas State University, 2011)
The objective of this series of studies was to examine select factors that affect behavior of beef cattle grazing native-tallgrass rangelands. Mineral supplements with divergent palatability characteristics were delivered to beef cows grazing native tallgrass range during various seasons of the year in order to measure mineral intake, frequency of supplement use, and duration of supplement use. We concluded that molasses-based mineral supplements influenced the activities of grazing cows more strongly than salt-based mineral supplements. These influences extended to the amount of supplement consumed as well as to the frequency, duration, and timing of use. Diet selection preferences of experienced, multiparous beef cows and naïve, primiparous beef cows grazing dormant, native tallgrass pastures were examined also during a short-term winter grazing bout. Naïve, primiparous cows selected more forbs and fewer grasses than experienced, multiparous cows. Previous research indicated that preference for broadleaf plants generally increased with grazing experience; however, these conclusions were based on research with greater-quality forages than those evaluated in our study. The differences in diet selection patterns between experienced, multiparous cows and naïve, primiparous cows during a short-term winter grazing period could be indicative of differences in long-term foraging strategies. In addition, the botanical composition of diets grazed by lactating beef cows with suckling calves and non-pregnant, non-lactating beef cows grazing either burned or unburned native tallgrass prairie during summer were evaluated. There were no differences in botanical diet composition between lactating cows suckling calves and non-lactating cows. In contrast, total graminoid selection was greater on burned (74.2%) than unburned pastures (71.8%) and total forb selection was greater on unburned (28.2%) than burned pastures (25.8%). We interpreted these data to suggest that forage selection preferences of beef cows can be altered with spring burning of native tallgrass pastures. Effects of large, round hay bale feeding method on intake of smooth bromegrass hay and eating behavior by beef cows were examined on dormant tallgrass prairie pastures during winter. Three large, round hay bale-feeding systems were evaluated: bales fed in a ring feeder, bales unrolled on the ground, and bales chopped with a flail-type hay processor (20-cm particle length) and deposited on the ground. Hay intake, hay refusal, frequency of use, and duration of use were not influenced by hay-feeding method. Foraging behaviors of beef cows in our studies were influenced by supplement type, cow age, and prescribed burning of rangeland. Conversely, foraging behaviors of beef cows were not influenced by lactation or by hay-feeding method.
Keywords: Beef cattle; Grazing behavior; Diet selection; Native range; Botanical composition; Supplementation; Animal Sciences (0475); Range Management (0777)